Adaptation of Higher Medical Education to the Conditions of Digitalization of Healthcare - V. A. Lazarenko; P. V. Kalutskiy; N. B. Dremova; A. I. Ovod (Высшее образование в России, 2020)
The aim of the work is to study the features of digitalization in medicine, healthcare, professional education, and to determine the directions of their further adaptation to the requirements of the time on the example of the medical university. The provision is based on the use of methods such as content analysis of modern publications on the problem, their logical analysis, generalization and systemization of published information, as well as the presentation of the experience of digitalization in the higher medical education.The article shows the relevance of digitalization for health care, with which it is possible to optimize the tasks of managing the quality and accessibility of medical care. They require a quick quantitative assessment using modern information technology, mathematical methods, software, big data analysis, and other technology tools. Content in digitalization in healthcare also includes the creation of innovative services and platforms that enable remote communication with patients, doctors, medical and pharmaceutical services, and the use of monitoring of medical and preventive processes in medical organizations.The digitalization of higher education is one of the areas of innovative policy of universities, implemented in accordance with the requirements and conditions of the external environment and own funds. Training of professionals with the right knowledge and digital technology requires appropriate educational information resources for educational and scientific processes in universities. To do this, the electronic information education environment (EIEE) is formed as a set of information, telecommunications and technology tools. The experience of creating EIEE at Kursk State Medical University over the past decades is presented. Various forms and methods of learning and knowledge control are being computerized. The university has subdivision management systems (dean’s offices, departments, library, staff, admissions committees, educational and methodological management and others). Many continuing medical education programs at the Faculty of Postgraduate Education are being implemented remotely. Methods and forms of practice-oriented and project-based training using information technology are being developed.